Analisis Efesiensi Tataniaga Kopi di Desa Ngarip Kecamatan Ulubelu Kabupaten Tanggamus - Mohammad Welly Justiceawan; Marlinda Apriyani; Fadila Marga Saty (Politeknik Negeri Lampung, 2020)
The research aimed to analyze coffee marketing channels in Ngarip Village, Ulubelu Subdistrict, Tanggamus Regency, analyze marketing margins , and analyze Marketing Efficiency . The method used was a survey method using questionnaires and the data that used were quantitative and qualitative data. The results of the study illustrated that there were 2 coffee marketing channels, named channel 1 (farmers - KUB - consumers) and channel 2 (farmers - collectors - KUB - consumers). The results of the marketing margin and Farmer's share show that marketing channel 1 marketing margin was (Rp. 17,730) and Farmer's share (98%) while marketing channel 2 marketing margin was (Rp. 17,730) and Farmer's share was (95%) ), this shows that marketing channel 1 was more efficient than marketing channel 2 because marketing channel 1 generated greater Farmer's share (98%) compared to farmer's share marketing channel 2 (95%)Keywords: Coffee, Farmer's Share, Marketing Channels, Marketing Efficiency, Marketing Margins.